Implementation of Business Model Canvas (BMC) in Supporting Digital Marketing in SKINBEAUTE Products after the Opening of Tiktok Shop - Ragita Widya Kartika; Sonja Andarini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research was conducted to find out and analyze the implementation of the Business Model Canvas (BMC) in supporting digital marketing in SKINBEAUTE products after the opening of the TikTok Shop. This research is qualitative research with a descriptive approach. The sample withdrawal technique used is the purposive sampling technique. Data was collected by conducting observations, interviews, and documentation. The results of this study show that (1) SKINBEAUTE is expected to evaluate previous operational performance to determine new strategies in the future through assessments from owners, employees, and consumers; (2) In mapping SKINBEAUTE's business conditions, there is a need for updates or improvements in several elements such as channels, key activities, key resources, key partnerships, and cost structures.